Coronavirus pandemic: an opportunity to study the anthropogenic impact on micro-climate conditions and CaCO3 crystal morphology in the Nerja Cave (SE Spain) - Liñán-Baena, Cristina; Jiménez de Cisneros, Concepción; Benavente, José; Vadillo-Pérez, Iñaki; Del Rosal Padial, Yolanda Remedios; Ojeda, Lucía (Elsevier, 2023)
Following the declaration of the COVID-19 pandemic, the Spanish Government restricted non-essential movements of all citizens and closed all public spaces, such as the Nerja Cave, until May 31, 2020. This particular condition of the closure of the cave provided a unique opportunity to study the micro-climate conditions and carbonate precipitation in this tourist cave without the presence of visitors. Our results show the significant effect of visitors on the air isotopic signature of the cave and on the genesis of the extensive dissolution features affecting the carbonate crystals formed in the tourist sector of the cave, alerting us to the possible corrosion of the speleothems located there. The movement of visitors within the cave also favours the mobilisation of aerial fungi and bacterial spores and their subsequent sedimen- tation simultaneously with the abiotic precipitation of carbonates from the drip water. The traces of these biotic elements could be the origin of the micro-perforations previously described in the carbonate crystals formed in the tourist galleries of the cave, but they are subsequently enlarged due to abiotic dissolution of the carbonates through these weaker zones.
Keywords: Cueva de Nerja (Málaga); Microorganismos; Anthropogenic impact; Carbon dioxide; Carbonate precipitate; COVID-19; Micro-organism; Tourist cave